LABORATORY PERFORMANCE OF ASPHALTIC CONCRETE WEARING COURSE (ACÃÆÃâÃâÃâWC) CONTAIN RETONA BLEND 55 ASPHALT WITH FILLER MODIFIED - JHON PHILIP S. (NIM 26906001); Pembimbing: Prof. Dr. Ir. Bambang Sugeng. S, DEA., dan Ir. Tit, FREDY
The resistance of pavement to heavy traffic loading, high temperature and environmental conditions, was influenced primarily by its component (asphalt) in the mixture. The usage of Retona Blend 55 in Asphaltic Concrete (AC-WC) mixture was expected to improve the weakness of Petroleum Asphalt (Pen 60/70). Laboratory research was conducted to determine the characteristic of Retona Blend 55 and to compare it with the Asphalt Pen 60/70. The experiment was conducted also to characterize the Asphalt Concrete (AC-WC) mixes using 2 (two) fillers types i.e. fly ash and portland cement (PC). The gradation used in the research is the gradation crossing the Fuller's curve and lying below the restricted zone. The specification used was the Indonesian Specification for Hot Mix Asphalt (2007). Using the Marshall's method, the OBC value obtained was 5.32% for AFA (Pen 60/70 + fly ash filler), 5.45% for APC (Pen 60/70 + portland cement filler), 6.18% for RFA (Retona Blend 55 + fly ash filler), and 6.25% for RPC (Retona Blend 55 + portland cement filler). The results of Marshall Immersion test show that all mixture satisfied the criterion of Index of Retained Stability (IRS) i.e. 96.41% for AFA, 96.03% for APC, 98.05% for RFA and 97.38% for RPC. The minimum value in the specification was 75% for Asphalt Concrete using Pen 60/70 and 80% for Asphalt Concrete using Retona Blend 55. The results of UMATTA test showed that the Resilient Modulus of RFA (1939 MPa and 1039 MPa) was higher than the RPC (1910 MPa and 959 MPa) for two temperatures (35oC and 45oC). While the Resilient Modulus of APC (1802 MPa dan 693 MPa) was higher than the AFA (1554 MPa dan 564.6 MPa). The results of Wheel Tracking test for two temperatures (45oC and 60oC) showed that mixture using fly ash filler gave the better resistance to permanent deformation, compared to the mixture using portland cement filler. The value of Dynamic Stability for two temperatures (45oC and 60oC) was 7000 passes/minute and 2250 passes/minute (AFA mix), 6300 passes/minute and 1901.1 passes/minute (APC mix), 7875 passes/minute and 4846.2 passes/minute (RFA mix) and 7000 passes/minute and 4846.2 passes/minute (RPC mix). In general, referring to all results of laboratory test (Resilient Modulus, Dynamic Stability and Index of Retained Stability), it was shown that the RFA mixture has the best performance comparing to the other mixtures (RPC, AFA and APC).